EFISIENSI PEMASARAN KOPRA DI DESA PICUAN BARU KECAMATAN MOTOLING KABUPATEN MINAHASA SELATAN (Marketing Efficiency of Copra in Picuan Baru Village, MotolingSub District, South Minahasa Regency) - Erwin Spancer Tendean; Benu Olfie L. S.; Ellen G. Tangkere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
The objective of this research is to find out how the marketing channels and copra marketing efficiency in Picuan Baru Village based on the marketing margin and farmer's share. This research was conducted for 8 months in October 2019 until June 2020. This study uses primary and secondary data. Primary data was obtained by submitting a list of questions to 10 Farmers and 5 Collecting Traders in Picuan Baru Village, Motoling Sub District, South Minahasa Regency. Secondary data was obtained from related institutions and sources that have relevance in this study. Sampling uses a purposive sampling method and snow ball sampling is a sample taken intentionally and uses a technique to determine respondents in a chain. The research result showed that copra marketing channels formed in the marketing of Picuan Baru Village, Motoling Subdistrict, South Minahasa Regency, obtained that there were two forms of marketing channels and farmer's share value obtained from the analysis results, namely in marketing channel I of 90.77% and in marketing channel II at 92.64%. The marketing marginÂ  of marketing channel I was Rp. 649.5 / kg and marketing channel II was Rp. 500 / kg.Keywords: Copra, Marketing Channel, Marketing Efficiency